Speech Genres in Marxism and the Philosophy of Language - Souza, Geraldo Tadeu (The ESPecialist, 2012)
This article tries to point out the need to take into account Bakhtin/Volochinov’s book Marxism and the Philosophy of Language in the reflections on Bakhtin’s and his circle’s ideas about genre. Therefore, we compare editions of this book in various languages, showing that, unlike the Brazilian edition, they present and show the importance of this category for reflections on the concrete reality of language.